Directions for implementing BDI agents in embedded systems with limited hardware resources - Santos, Matuzalem Muller dos; Hübner, Jomi Fred; Brito, Maiquel de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2021: Anais do XV Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2021)
The characteristics of autonomy, reactivity, and proactivity, commonly present in embedded systems used in cyber-physical systems, are often similar to the ones of agents. Although the usage of agents in these scenarios would be beneficial, the lack of tools to implement agents in hardware commonly used in low-cost embedded systems is one of the reasons that prevent embedded agents from becoming a reality. This paper discusses some implementation challenges and design considerations required to develop a framework that allows implementing BDI agents in embedded systems.